Effect of Lycopene on Peritoneal Fluid Malondialdehyde Level in Endometriosis - Astarto, Nanang W.; Djuwantono, Tono; Yelliantty, . (Maranatha Christian University, 2015)
Oxidative stress is a factor that contribute in pathogenesis of endometriosis. This condition could also implicated in infertility. Lycopene is a carotenoid that has antioxidant activity. Supplementation of lycopene can reduce oxidative stress in peritoneal fluid of women with endometriosis. This study aims to compare the effect of lycopene on malondialdehyde (MDA) levels in peritoneal fluid of women with endometriosis. It is an experimental study on peritoneal fluid from five women with endometriosis. The result show that lycopene supplementation affecting the MDA levels in peritoneal fluid. MDA levels in peritoneal fluid with lycopene is lower than without lycopene. It conclude that lycopene is proved lowering MDA levels in peritoneal fluid of women with endometriosis.Â Keywords: endometriosis lycopene, malondialdehyde